Beyond Bureaucratic Rigidity: A Dynamic Capability Framework for Public Sector Disaster Response - Kristian, Indra; Kurniawan, Yudiyanto Tri; Khaerani, Thalita Rifda; Pramana, Iwan; Marbun, Frederic Kornelius (Department of Public Administration, 2025)
This study investigates how public institutions apply dynamic capabilities in disaster management to strengthen adaptability and resilience. The research focuses on institutions such as BNPB and BPBD, collecting data through in-depth interviews, field observations, and document analysis using a qualitative case study approach. Grounded theory elements guide the inductive development of a conceptual framework based on three key components: sensing, seizing, and transforming. The study finds that traditional bureaucratic structures often rigid and hierarchical are poorly suited to handle the fast-paced and complex nature of disasters. Institutions that can detect early signals, coordinate strategic actions, and adapt organizational routines in real time show greater responsiveness. Key enablers of this capacity include technological integration, inter-agency collaboration, and continuous learning processes. The research contributes theoretically by contextualizing the dynamic capabilities framework within public governance, moving beyond its original business-oriented formulation. It offers insights for institutional reform by identifying adaptive patterns in disaster response that can inform more flexible, data-driven, and sustainable emergency governance models. These findings provide a foundation for improving the agility of public institutions in navigating future uncertainties and crisis environments.